A cognitive semantic analysis of english and arabic verbs of visual perception ‘see’ and ‘ra’a’ in fiction writing - Jumaah, Aldawoodi Ruaa Talal (2019)
Sweetser (1990) claims that vision is the prime sense organ that motivates metaphors of intellect, such as ‘knowing’, ‘understanding’ and ‘thinking’. She also asserts that these metaphors are cross-cultural phenomena, possibly universal in human thoughts and speech. In the light of this claim, this study focuses on whether the metaphors of visual perception are really as universal as has been argued in the literature as research in non-Western languages has demonstrated that the metaphors are not universal. Thus, this study aims: 1) To unravel the conceptual metaphors underlying the linguistic expressions of the English and Arabic verbs of visual perception see and ىأر (ra’a) in fiction writing, 2) To compare the conceptual metaphors underlying the linguistic expressions of the English and Arabic verbs of visual perception see and ىأر in fiction writing, 3) To examine how human physiology motivates the conceptual metaphors underlying the English and Arabic verbs of visual perception see and ىأر , and 4) To determine the role of culture in the motivation of conceptual metaphors underlying the English and Arabic verbs of visual perception see and ىأر .